2022
DOI: 10.1177/09697330221085770
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress and moral resilience of nurse managers

Abstract: Background Moral distress is a phenomenon that can lead to an imbalance of the mind and body. There are many coping strategies to overcome the obstacles that lead the subject to this condition. Some coping strategies are capable of being achieved through the cultivation of moral resilience. Aim The aim is to identify the strategies of moral resilience in the nursing management of University Hospitals in Brazil. Research design The research design is the qualitative study with discursive textual analysis. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 50 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…All reviewed articles indicated that nurse leaders experience MD regardless of their leadership role and responsibility. [41][42][43][44][45][46] The consuming nature of MD is best reflected by the descriptive themes "impacts on wellbeing" and "impacts on the organization and quality of patient care." These impacts, at times, were detrimental for the nurse leader.…”
Section: Theme 1: Moral Distress Is Consumingmentioning
confidence: 99%
See 4 more Smart Citations
“…All reviewed articles indicated that nurse leaders experience MD regardless of their leadership role and responsibility. [41][42][43][44][45][46] The consuming nature of MD is best reflected by the descriptive themes "impacts on wellbeing" and "impacts on the organization and quality of patient care." These impacts, at times, were detrimental for the nurse leader.…”
Section: Theme 1: Moral Distress Is Consumingmentioning
confidence: 99%
“…I think they make me more aware of my role, because my attitudes in the workplace interfere with other people's lives." (NM11) 44 Personal Support and Organizational Empowerment: Seeking guidance from peers and colleagues external to their organization and from friends and family was reported by some nurse leaders as a mitigating factor to their MD. 41 Psychological protection by the organization was an important component nurse leaders reported from within their organizations.…”
Section: Theme 1: Moral Distress Is Consumingmentioning
confidence: 99%
See 3 more Smart Citations